Optical properties of ferroelectric photonic structures. (25th April 2020) - Bi, D.; Gorelik, V. S.
Abstract: The optical properties of KIO3 photonic structures of various types were studied in this article. The composite photonic materials used were based on opal photonic crystals, monodisperse silica nanoparticles, and diamond microparticles, respectively. The size effect of the Raman intensity in these structures was investigated. At a certain size of globules or particles, the Raman intensity of ferroelectric photonic structures was greater than the initial Raman spectral intensity of KIO3 .